Nitric oxide accelerates mycorrhizal effects on plant growth and root development of trifoliate orange - Tian, Li; Nasrullah,; Huang, Xiao-Yun; Wu, Qiang-Sheng (Penerbit Universiti Kebangsaan Malaysia, 2017)
Arbuscular mycorrhizal fungi (AMF) actively colonize plant roots and thus enhance plant growth through different mechanisms. In the present study, trifoliate orange (Poncirus trifoliata) seedlings inoculated with Diversispora versiformis were subjected to 0 and 0.2 mmol/L sodium nitroprusside (SNP, a nitric oxide donor) treatments. After eight weeks, exogenous SNP considerably increased root mycorrhizal colonization by 25%, showing a positive stimulating effect of NO on mycorrhizal formation. Mycorrhizal inoculation significantly increased plant growth performance (height, stem diameter, leaf number and shoot and root dry weight) and root traits (length, projected area, surface area, volume and number of 2nd and 3rd order lateral roots) than non-mycorrhizal treatment and NO (exogenous SNP treatment) heavily strengthened the mycorrhizal effects. Moreover, NO and mycorrhization induced more fine root (0-0.5 cm) formation. There was an opposite changed trend in root sucrose and leaf and root glucose contents by SNP in AMF versus non-AMF seedlings. All these results implied that NO plays important roles in mycorrhizal formation and development and also accelerates mycorrhizal effects on plant growth and root development of trifoliate orange.